(untitled) (Journal of the College of Basic Education, 2022)
The research adopted by the psychological sciences described the research of aesthetic tasting by adopting social and physiological references *, and in particular the research in the aesthetics of the psychological dimension of the animal in the human self, and among the scenes the impact of its reflection on the formation of contemporary American ceramics, as it developed several descriptions, which reached in their interpretations a metaphysical level I nodded behind the experience. In addition, the psychological dimension of the animal in the human self is an exciting and provocative form of human taste in general. This is due to the association of this formation with intellectual, physical and natural references